Решение уравнений: 1) (25/9)^x*(27/125)^x-5= 5/3 2) (5/6)^x^2-2x=(5/6)^6-x 3)2^1-x^2*2^2x=64^-1

Решение уравнений: 1) (25/9)^x*(27/125)^x-5= 5/3 2) (5/6)^x^2-2x=(5/6)^6-x 3)2^1-x^2*2^2x=64^-1
Гость
Ответ(ы) на вопрос:
Гость
1.  (25/9)^x *(27/125)^(x-5)=5/3,  ((5/3)²)^x *((3/5)³)^(x-5)=5/3 (5/3)^(2x) *(3/5)^(3x-15)=5/3,   (5/3)^(2x)*((5/3)⁻¹)^(3x-15)=5/3 ((5/3)^(2x))*((5/3)^(-3x+15))=5/3,    ((5/3)^(2x-3x))*((5/3)¹⁵)=5/3 (5/3)^(-x)=(5/3):(5/3)¹⁵,      (5/3)^(-x)=(5/3)⁻¹⁴ -x=-14, x=14 2.   (5/6)^(x²-2x)=(5/6)^(6-x) x²-2x=6-x, x²-x-6=0, x₁=3, x₂=-2 3. 2^(1-x)*2^(2x)=64⁻¹ 2^(1-x+2x)=(2⁶)⁻¹ 2^(1+x)=2⁻⁶ 1+x=-6, x=-7
Не нашли ответ?
Ответить на вопрос
Похожие вопросы